Implementing the Humanistic Approach in 21st-Century Interactive Arabic Language Learning at Madrasah Ibtidaiyah - Lestari, Yuni; Muhtarom, Yusuf; Maksudin , Maksudin (Language, Technology, and Social Media, 2023)
The purpose of this study is to elucidate the paradigm of the humanistic approach in 21st-century interactive Arabic language instruction at Madrasah Ibtidaiyah. This research employs a library research methodology, sourcing data from literature, various websites, journals, dictionaries, encyclopedias, documents, and magazines. The findings demonstrate that the humanistic approach is instrumental in helping students comprehend Arabic by integrating contemporary digital learning developments. This approach focuses on nurturing students' cognitive, affective, and psychomotor skills through a supportive and engaging educational environment. The study highlights the necessity of this approach in overcoming the challenges students face in learning Arabic, ensuring a more enjoyable and less daunting learning experience. The humanistic approach serves as a strategic framework to facilitate effective Arabic language acquisition, aligned with the demands of 21st-century education.